Effect of laser loop on surface morphology of copper substrate and wettability of solder joint - Roduan, Siti Faqihah; Wahab, J. A.; Aiman, M. H.; Zaifuddin, A. Q.; Mohd Salleh, M. A. A.; Mahadzir, I. (IOP Publishing Ltd, 2019)
The effect of different laser loop parameter on the geometry of micro-groove pattern on copper substrate and its effect on the wettability was investigated. The micro-grooves pattern was fabricated on the copper surface through laser surface texturing process. 3D measuring laser microscope and contact angle measurement test was conducted to measure the geometry of the micro-grooves pattern and wettability of the solder joint respectively. The results showed that the improvement in laser loop parameter increased the depth of the micro-grooves due to the more exposed time which allows more material ablation. It also showed that the contact angle of textured substrate is smaller than the untextured substrate which results in better wettability.